The Effect of Work-From-Anywhere and Digital Well-Being on Work-Life Harmony with the Mediation of Employee Involvement to Improve Performance Efficiency at Lampung Post Company - Zul Hendri; Febrianty; Muhammad Irfan Pratama (Danadyaksa: Post Modern Economy Journal, 2026)
The development of digital technology has changed the conventional work paradigm towards a flexible Work-From-Anywhere (WFA) system that requires adaptation to digital well-being and work-life harmony. In the context of media organizations such as Lampung Post, this change poses challenges to performance efficiency due to the high digital workload and the need for flexible working hours. This study aims to analyze the influence of WFA, Digital Well-Being, and Work-Life Harmony on performance efficiency with employee engagement as a mediating variable. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Square (SEM-PLS) method, involving Lampung Post employees as research respondents. The analysis results show that the three independent variables have a positive and significant effect on performance efficiency, both directly and indirectly through employee engagement. Work-Life Harmony has the most dominant influence, while employee engagement is proven to be the main mediator in strengthening the relationship between variables. This study concludes that improving performance efficiency in the digital work era depends on the synergistic management of work flexibility, digital well-being, and work-life harmony with employee engagement as the main driver.